(untitled) (Acta Scientiarum. Education, 2015)
This paper addresses the primary public inspection, particularly that exercised by parish inspectors, considered as one of the forms of manifestation of the policy on education. A research about reports and official letters concerning the primary public education in Paraná in the provincial period (1853-1889) shows ordinary school issues and, especially, the relationship between teachers and the authorities responsible for the administration and control of the work in schools. This paper aims to deep the knowledge on parish inspection and literary council, as components of the inspection that used to be present in the relations between teachers and inspectors. The methodology includes documental research, analysis of sources and crossing of information from reports and official letters with the provincial legislation of Paraná. We can conclude that, in spite of a relative legal organization when it comes to the distribution of administrative functions and control over public instruction, the latter remained quite precarious at the end of the provincial period, since only with the advance of social relations of production of material life the school would become necessary.